Logistic convergence as a mechanism of modification the system of management accounting of import operations at enterprises - Shmatko, Nataliia; Bondarenko, Andrii; Kaliuha, Yevheniia; Kozachenko, Liliіa; Shevtsiv, Liubov; Sedikov, Denys (My University, 2020)
The lack of methodological and organizational bases for the formation of management accounting of import operations at enterprises determine the need and relevance of a systematic study of this problem. The article deals with the introduction at the enterprise of management accounting of import operations, which will allow to provide an adequate reflection of the perfect facts of import operations, a visual reflection of the economic essence of import operations, the construction of a real picture of the financial results obtained by the organization and optimization of the use of resources, and the reduction of accounting errors with duplicate information of different accounting systems. Besides, it is proposed to build management accounting based on IFRS, which in turn will allow attracting foreign investors; will significantly reduce material and time costs when compiling international standards. The logic of the research consists in moving from assessing the main trends in the use of logistics in the foreign economic activity of an enterprise, modern approaches to management accounting, economic conditions and the possibilities of using logistics.
Keywords: accounting automated system; contract; customs declaration; enterprise; import operations; logistic convergence; management accounting